An efficient approach to 4-chloro quinolines via TMSCl-mediated cascade cyclization of ortho-propynol phenyl azides. Issue 9 (28th March 2018) - Song, Xian-Rong; Li, Ren; Ding, Haixin; Chen, Xi; Yang, Tao; Bai, Jiang; Xiao, Qiang; Liang, Yong-Min
Abstract : A novel and efficient strategy for the synthesis of 4-chloro quinolines via the TMSCl-mediated cascade cyclization of easily prepared ortho -propynol phenyl azides is developed. Abstract : A novel and efficient strategy for the synthesis of 4-chloro quinolines via the TMSCl-mediated cascade cyclization of easily prepared ortho -propynol phenyl azides is developed. This reaction proceeds smoothly in moderate to excellent yields with a wide range of substrate compatibility. TMSCl acted not only as a promoter, but also as a chloro source in this transformation. Moreover, the obtained 4-chloro quinolines could be further derivated in an array of palladium-catalyzed coupling and nucleophilic substitution reactions to construct potential biologically active and pharmaceutical molecules.